2018
DOI: 10.1186/s12884-018-1816-z
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and barriers to physical activity in overweight and obese pregnant women: an analysis informed by the theoretical domains framework and COM-B model

Abstract: BackgroundObesity during pregnancy is associated with increased risk of gestational diabetes mellitus (GDM) and other complications. Physical activity is a modifiable lifestyle factor that may help to prevent these complications but many women reduce their physical activity levels during pregnancy. Interventions targeting physical activity in pregnancy are on-going but few identify the underlying behaviour change mechanisms by which the intervention is expected to work. To enhance intervention effectiveness, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
191
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(210 citation statements)
references
References 66 publications
9
191
0
5
Order By: Relevance
“…This study identified no differences in physical activity levels between women with and without GDM in the interval following GDM screening. The lack of change in physical activity for both groups aligns with reported barriers to physical activity for such women including a lack of time, pain, fatigue, work and childcare commitments [27].…”
Section: Discussionmentioning
confidence: 57%
“…This study identified no differences in physical activity levels between women with and without GDM in the interval following GDM screening. The lack of change in physical activity for both groups aligns with reported barriers to physical activity for such women including a lack of time, pain, fatigue, work and childcare commitments [27].…”
Section: Discussionmentioning
confidence: 57%
“…Behaviour Change Techniques are the active, observable and replicable components that make up an intervention. COM-B/BCW have been used successfully for behavioural analysis and to design interventions in both health and non-health-related elds [26,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], but to our knowledge, has been used in only one study of TB on contact tracing in a low-resource setting, to identify barriers and facilitators and to tailor interventions to improve contact investigation in Kampala [26]. In the qualitative arm, to understand the challenges in recognising and testing for TB in admitted children we analysed data from: i) semi-structured interviews, small-group discussions and key informant interviews with front line health workers and mid-level managers; ii) observations of TB trainings, sensitisation meetings, policy meetings, and hospital practices, and iii) desk review of guidelines, job aides and policy documents, which have been reported elsewhere [31].…”
Section: Using the Behaviour Change Wheel To Guide Intervention Designmentioning
confidence: 99%
“…The TDF [38], compromises 14 domains, each of which corresponds to a COM-B component and also representing a range of theory-based barriers and facilitators to behaviour [37]. The COM-B model and TDF have been used by several studies to explore barriers and facilitators to behaviour change in sexual health [42], physical activity in obese pregnant women [43] and reducing sugar [40]…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To our knowledge, this is the first study investigating adherence to the MIND diet at midlife (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) years old) in a Mediterranean and non-Mediterranean country. This study addresses this gap in the literature and highlights the perceived barriers and facilitators to adhering to a diet that may promote brain health at midlife and compares those barriers and facilitators to those living in Northern Ireland.…”
Section: Introductionmentioning
confidence: 99%